Educação e sustentabilidade: potencialidades e desafios à formação de espaços educadores sustentáveis - Faraco, Cristina Machado Oliveira (2017)
In the current context of social and environmental crisis, the formation and organizing of sustainable teaching spaces is becoming a necessary reality. The objective of the present work is to foster an understanding of how to create and organize such spaces in the Brazilian context by examining the potential and challenges revealed in three such existing spaces: NaturGut Ophoven in Germany and Pousada Vitória and Gaia Village in Santa Catarina, Brazil. Qualitative phenomenological research included documentary study (folders, reports, websites, and booklets), participant observations of educational activities, the researcher's field diary, and semi-structured interviews with the coordinators of the sites visited. Interpreting the information involved recording and describing the experiences, extracting all significant assertions, formulating meaning from the raw data, and organizing these concepts into thirteen common themes that were then distilled into four textual groups. Those four groups are related to the origin and the guidelines of the sustainable teaching spaces (in the thinking of the subjects), structure (human potential, physical and economic structure); processes (environmental education, sustainability, topics studied, activities carried out, and future projects); and the challenges encountered. The information that emerges from this study emphasizes that: sustainable educational spaces may be conceived in, as well as emerge from, different origins in widely different landscapes (urban, rural, forest, or coastal), and may be supported by differing theoretical and practical bases, and some may even assume different forms while employing substantially different processes. In implementing this approach it is important to consider: the origin of materials (whether the materials and structures used are friendly to the environment and thus to society); how to properly dispose of generated waste; the necessity of identifying possible alternatives to save, produce, and optimize energy; and even how the buildings might be organically integrated into the natural landscape. In terms of processes: implementers must examine integrated relationships between individuals (and theirs with the environment), organic agriculture and sustainable management in animal husbandry, experiences in museums, living spaces and outdoors, and processes of human inclusion (such as people with disabilities, low-income people, and immigrants), environmental education processes in critical, transformative, and emancipating ways, and all the above supervised by researchers in this area. The challenges common to the spaces visited tend to be related to: obtaining resources for the construction of structures, general financing for the projects, and achieving funds for maintaining those activities for which they have been created. Such challenges indicate, in many cases, the need for attracting governmental entities as potential sources of aid. They also point to the importance of sensitive living in the environment, changing relationships and patterns of consumption, submitting projects to the sources of development, and fundamentally rethinking the training of educators with a view to a more critical and essential approach.